A corporate strategy for Jones Lang La Salle (Phils.), Inc. - Fajardo, Jaili Teresa M. (Animo Repository, 2001)
The objective of this paper is to develop a corporate strategy for Jones Lang LaSalle (Philippines) Inc., a firm engaged in providing property services. Jones Lang LaSalle is a leading global provider of comprehensive real estate and investment management services. The company serves clients locally, regionally and internationally from offices in over 100 markets in 33 countries in five continents. Drawing on the collective real estate skills, knowledge base and experience accumulated around the world over the years, the firm applies the expertise to anticipate changing client needs, interpret shifting market conditions and identify attractive opportunities. Jones Lang LaSalle has established its Philippine office last July 1997 at the same time that the financial currency turmoil has affected the country. Nevertheless, the company remained unfazed by the market situation and believes that there is potential in the Philippine market. The property services industry is comprised of large multinational companies that are privately owned which relies mostly on leasing commission fees from office and residential units. The industry is threatened by the slump in the economy which had the real estate industry badly hit. Coupled by the projected oversupply in the office space from the beginning of 2001 until 2002, fierce competition is seen to be the general outlook of the industry in the future. Nevertheless, the battle for survival and market share depends on the quality of services and products to be rendered in the market. Threats being experienced by the industry are: (a) unfair competition, (b) price competition, (c) in-country political situation, and (d) privacy. Opportunities are (a) increase in customer potential, (b) advancement in technology and (c) globalization and change in firm size. Strengths are (a) worldwide presence, (b) management strength and capabilities and (c) product flexibility. Weaknesses are (a) lack of IT infrastructure, (b) limited cash resource and (c) lack of conveyance of mission and vision. It is recommended that the generic objective of the company is to be known as the The Property Service Firm of the Future. It would be characterized by the global organization, vertically integrated company whose range of products and services- and whose presence in and knowledge of the world's real estate and capital markets- would allow the company to serve clients as a single source of solutions for all their real estate needs. Based on the proponents' strengths and weaknesses and the opportunities and threats to the industry, a corporate strategy is developed to attain the company's objectives. The generic competitive strategy recommended is cost leadership that should complement the foremost business objective to build Jones Lang LaSalle as The Property Services Firm of the Future. Functional strategies are as follows: Marketing will adapt an aggressive marketing strategy to promote the services of the company. Keeping the customers satisfied and making them feel that their needs are being addressed is one of the important factors in getting repeat jobs. This will contribute to the company's goal of increasing marketing share. Accounting and finance shall source out finds that will make possible the capital acquisitions and will also be closely monitoring budgets and implementing controls. They should be part of management planning activities for management to coordinate business strategy with current company resources. The human resources management will continuously provide support to its employees in improving their skills needed in the performance of their responsibilities. They would ensure that human resources policy and practice throughout the company and will develop targeted initiatives to ensure the human resource function is aligned to effectively support business. The department should also direct the development and implementation of programs in compensation and benefits, organizational planning and development, strategic staffing and recruiting, training and development and diversity to enhance the company's overall ability to attract and retain the talent necessary to win the marketplace. Information systems will be committed to the development of an open and advanced technology platform that promote and supports the real and broader business objectives of potential and existing clients. JLL would tap the power of the internet to aggregate purchases in the managed property portfolio: to invest in software applications for our project management and development management business and to offer clients online access to portfolio performance data. Property development will be developed as a department perceived as value-added. With the acquisition of ISO 9002 certificate of quality in all managed properties, it would develop a best in-class delivery model that includes a triad of interrelated sets of flex points-- organizational, operational and financial-- that overlap and are woven together to produce a cohesive, effective and efficient service. Finally, to effectively implement the proposed strategy and consequently, achieve the objectives, there should be common shared values among the employees. The corporate mission and vison should be shared with the employees so that together they can work with management to succeed. The corporate strategy recommended is then translated/implemented to the different levels and activities of the company's units using the 7s framework developed by McKinsey and Co.